2015
DOI: 10.1177/0741932515590234
|View full text |Cite
|
Sign up to set email alerts
|

Growth on Oral Reading Fluency Measures as a Function of Special Education and Measurement Sufficiency

Abstract: Oral reading fluency (ORF) was investigated initially by Deno, Mirkin, and Chiang (1982) with a plethora of studies published since then (Tindal, 2013). As originally designed, ORF was to provide teachers a systematic way to monitor the effects of instruction over time. In the early days, passages were drawn at random from a curriculum series representing a "long range goal" level of difficulty (to be covered within the year) that inherently provided preview and review of material (Fuchs & Deno, 1994). Althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 42 publications
4
15
0
Order By: Relevance
“…The results of this study suggest that the variability around the slope for progress monitoring may be considerably smaller than in previous studies (e.g., Briggs, 2011; Christ, 2006) as measured by the highest and lowest readability progress monitoring passages for second, third, and fourth grade in DIBELS Next (Good & Kaminski, 2011) read by students who are at risk in reading. We found that students’ CWPM grew by approximately 1 word per minute per week, which is similar to previous research on the growth rates for students who are at risk for reading difficulties (e.g., Deno, Fuchs, Marston, & Shin, 2001; Fuchs et al, 1984; Tindal et al, 2016). In addition, this growth was statistically significant and almost 4 times higher than the error around that slope.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The results of this study suggest that the variability around the slope for progress monitoring may be considerably smaller than in previous studies (e.g., Briggs, 2011; Christ, 2006) as measured by the highest and lowest readability progress monitoring passages for second, third, and fourth grade in DIBELS Next (Good & Kaminski, 2011) read by students who are at risk in reading. We found that students’ CWPM grew by approximately 1 word per minute per week, which is similar to previous research on the growth rates for students who are at risk for reading difficulties (e.g., Deno, Fuchs, Marston, & Shin, 2001; Fuchs et al, 1984; Tindal et al, 2016). In addition, this growth was statistically significant and almost 4 times higher than the error around that slope.…”
Section: Discussionsupporting
confidence: 89%
“…The data were analyzed using a two-level repeated measures growth model (Holt, 2008) using HLM 7 (Raudenbush, Bryk, & Congdon, 2011). Students’ weekly CBM ORF scores (CWPM) were nested within student (Briggs, 2011; Hintze & Christ, 2004; Tindal et al, 2016). Although ordinary least squares (OLS) analysis has been used in previous studies on CBM growth (e.g., Christ, 2006), OLS requires that all students receive assessments on the same time schedule and that all students receive the same number of assessments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Abdurrahman ( 2003) said that students with learning disabilities is a learning difficulty that associated with development learning disabilities, included: a motor disorder, p learning difficulties in the adjustment of social behavior, and the difficulty of academic learning which include : reading , writing and mathematics. This finding was similar to that of Alonzo (2016), who found that performance on measu special education status The types of reading that need to be mastered by students according to is reading fluently, intensive reading, reading languages, and reading quickly. The large number of students with disabilities who experience reading difficulties, as well as students who may not be eligible for special This study aims to determine the effect of videoscribe for improving reading fluently ability for learning disability.…”
Section: Introductionsupporting
confidence: 86%
“…If we compare our findings with growth rates found in studies of English readers, we see that the Norwegian students began the year reading fewer WCPM but experience stronger growth during the school year. For instance, Tindal, Nese, Stevens, and Alonzo () found that U.S. students in grade 3 began the year reading an average of nearly 81 WCPM (15 WCPM more than Norwegian students), just above 100 WCPM in grade 4 (three WCPM more than Norwegians), and 125 WCPM in grade 5 (21 WCPM more than Norwegians). The slope in each of these grades ranged between 0.65 and 0.73 WCPM, whereas the slope in the Norwegian grades 3–5 ranged between 0.76 and 0.84 WCPM.…”
Section: Discussionmentioning
confidence: 99%